Cinzas do Brasil: esmaltes cerâmicos do bagaço de cana-de-açúcar - Murakawa, Vanessa Yoshimi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The use of plant ashes in ceramic glazes comes from ancient time. Originated in the East, this technique has been used by several contemporary ceramists in Brazil and stands out as an aid to sustainable development, as it works with reuse of materials. Throught the fire, dry leaves, grass cuttings and waste organic material can be turned into ashes and used in the composition of these glazes. This research aims to continue the study related to the use of plant ashes in the composition of ceramic glazes, investigating in particular the ash from the sugarcane bagasse. Also, aims to research the possibilities of glazing through trials with sugarcane bagasse ashes from a power plant in different clays and firing kilns, as well as a the historical production of ceramics in Eastern coutries (China, Korea and Japan), where the technique was initiated and developed, until the potters that use this unameling technique in Brazil.

A utilização de cinzas vegetais em esmaltes cerâmicos vem de tempos remotos. Com origem no Oriente, a técnica vem sendo utilizada na contemporaneidade por vários ceramistas no Brasil e se destaca no auxílio ao desenvolvimento sustentável, pois trabalha com a reutilização de materiais. Através do fogo, folhas secas, podas de grama e resíduos de material orgânico podem ser transformados em cinzas e utilizados na composição desses esmaltes. Essa pesquisa vem dar continuidade ao estudo relacionado à utilização de cinzas vegetais na composição de esmaltes cerâmicos, investigando em especial as cinzas do bagaço da cana provenientes de uma usina, realizando queimas em diferentes argilas e fornos, além de um resgate histórico de produção de cerâmica dos países do Oriente (China, Coréia e Japão), onde a técnica teve início e se desenvolveu, chegando aos ceramistas que utilizam essa técnica de esmaltação no Brasil.
Keywords: Esmaltes; Ceramica; Bagaço de cana; Sustentabilidade; Sustainability